Politeness Strategies of Suggesting Utterances by the First Semester Students of English Department of Muhammadiyah University of Surakarta - Fitri Astuti, Sonia; , Dra. Siti Zuhriah Ariatmi, M.Hum (2017)
This research aims at describing the strategies of suggesting and the realization of politeness strategy of suggesting strategies used by the first semester students of English Department of Muhammadiyah University of Surakarta. The data used in this research are utterances which are used by the first semester students. The researcher use Discourse Completion Task (DCT) to collect the data. The techniques of analyzing data are making the DCT scenario, documenting the data, analyzing the findings and drawing conclusion. The data are analyzed by using the theory of suggesting strategy (Flor, 2005) and theory of politeness (Brown and Levinson, 1987). The researcher found that: (1) there are three types of suggesting strategies used by the students namely; direct suggestion takes 15%, conventionalized form takes 34%, indirect suggestion takes 1%. The utterances which do not belong to suggesting strategy take 50%. There are 22% of the students who use the suggesting strategy appropriately, and 78% of the students use suggesting strategy inappropriately because they fail to choose the appropriate suggesting strategy in relation with the power property of the speakers, the distance among the speakers and the seriousness of the case that makes them are over polite and impolite, (2) there are four types of politeness strategies used by the students namely: bald-on record takes 30%, positive politeness takes 36%, negative politeness takes 23%, bald off record takes 3%. The utterances which do not belong to politeness strategy take 9%. There are 36% of the students who use politeness strategy appropriately and 64% of the students use politeness strategy inappropriately because they fail to choose the appropriate politeness strategy in relation with the power property of the speaker, the distance among the speakers and the seriousness of the case.